2006
DOI: 10.1111/j.1529-8817.2006.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENETIC ANALYSES OF THE BRYOPSIDALES (ULVOPHYCEAE, CHLOROPHYTA) BASED ON RUBISCO LARGE SUBUNIT GENE SEQUENCES1

Abstract: Current taxonomy of the Bryopsidales recognizes eight families; most of which are further categorized into two suborders, the Bryopsidineae and Halimedineae. This concept was supported by early molecular phylogenetic analyses based on rRNA sequence data, but subsequent cladistic analyses of morphological characters inferred monophyly in only the Halimedineae. These conflicting results prompted the current analysis of 32 taxa from this diverse group of green algae based on plastid-encoded RUBISCO large subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 39 publications
10
67
0
1
Order By: Relevance
“…DNA amplification followed previously published protocols (Famà et al, 2002;Hanyuda et al, 2000;Karol et al, 2001;Kooistra, 2002;Lam and Zechman, 2006;Olson et al, 2005;Wolf, 1997), with additional primers for amplification of partial sequences of the rbcL gene and the 16S rDNA. A complete overview of the primers used is given in Fig.…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA amplification followed previously published protocols (Famà et al, 2002;Hanyuda et al, 2000;Karol et al, 2001;Kooistra, 2002;Lam and Zechman, 2006;Olson et al, 2005;Wolf, 1997), with additional primers for amplification of partial sequences of the rbcL gene and the 16S rDNA. A complete overview of the primers used is given in Fig.…”
Section: Data Generationmentioning
confidence: 99%
“…cylindracea) that are known to have profoundly affected the ecology and native biota in areas of introduction. Molecular phylogenetic studies have shown two principal bryopsidalean lineages, both comprising simple as well as complex forms (Lam and Zechman, 2006;Verbruggen et al, 2009;Woolcott et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A single genus, Dichotomosiphon, occurs in freshwater habitats. A phylogeny based on rbcL sequence data (Lam & Zechman, 2006) revealed two main clades, corresponding to the suborders Bryopsidineae and Halimedineae, which are characterized based on differences in thallus morphology, reproduction and plastid types (Hillis-Colinvaux, 1984). Increased gene and taxon sampling improved phylogenetic resolution in these clades and revealed the limestone-boring genus Ostreobium as an early diverging lineage .…”
Section: Ulvophyceaementioning
confidence: 99%
“…Second, the more commonly used outgroup comparison method was applied to infer the root position. Sequences of a Bryopsis species (a sister genus of Codium; Lam and Zechman, 2006) and an Ostreobium species (a more distantly related bryopsidalean genus) were added to the concatenated alignment. The alignment was analyzed with each of the outgroup sequences separately and together using GTR + C + I models as specified in Appendix 5.…”
Section: Tree Rootingmentioning
confidence: 99%